Studi Komparasi Strategi Picture And Picture Dengan Mind Mapping Terhadap Hasil Belajar IPS Siswa Kelas IV SD Muhammadiyah PK Pracimantoro Tahun 2015/2016 - EKOWATI, WIWIK, Drs. Muhroji, S.E.,M.Pd (2016)
This research is aiming at (1) differences the influence about the application of picture and picture's strategy with mind mapping's strategy auctioned in learning outcome of social science at the 4th grade students of Special Program Muhammadiyah primary school of Pracimantoro 2015/2016 academic year, (2) the bigger influence in learning outcome of social science between picture and picture's strategy with mind mapping's strategy. This research is experiment quantitative. The Subject of this research is all students at 4th grade of Special Program Muhammadiyah primary school of Pracimantoro 2015/2016 academic year. The tehnique of collecting data is test, documentation and interview. The tehnique of analizing data is t-test which doing pre-requisite test like homegenity test and normality test first. Based on the data analysis about 5% degree's significance the result shows ttet > ttable is 4,0858 > 2,000 which the average of the learning outcome at 4th grade A is higher than the learning outcome at 4th grade B, is 83,226 > 80. The conclusion is (1)there are differences in leraning outcome of social science using picture and picture's strategy and mind mapping's strategy auctioned in learning outcome. (2) mind mapping's strategy is bigger influence than picture and picture's strategy auctioned in learning outcome of social science.